The Effect of Functional Combustion on Job Satisfaction of Workers in the Lattakia Finance Directorate - ميّا علي; داؤد علا (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research aims to identify the level of the phenomenon of functional combustion with its dimensions (job exhaustion, low personal achievement, feelings of feelings) among workers in the financial directorate of Lattakia, and then study the effect of the level of this phenomenon on achieving job satisfaction among workers in the directorate. The research relied on the descriptive approach, and the research community included all workers in the Lattakia Finance Directorate, which numbered (1083) workers, while the research sample was determined using the Statistical Sample Law, and the questionnaire was distributed to the sample’s number of (284) workers, and was retrieved ( 251) Questionnaire, with a response rate of (88.38%). The results showed that there is a weak adverse and statistically significant effect of the job alienation of the employees in the financial directorate of Lattakia on achieving job satisfaction for them, as (32.8%) of the changes in job satisfaction were caused by the dimensions of the job alienation, and therefore the increased manifestations of job alienation among the workers in the financial directorate of Lattakia They lead to a low level of job satisfaction.